Regulatory roles of RpoS in the biosynthesis of antibiotics 2,4-diacetyphloroglucinol and pyoluteorin of Pseudomonas protegens FD6 - Zhang, Qing Xia; Xiong, Zheng Wen; Li, Shen Yu; Yin, Yue; Xing, Cheng Lin; Wen, De Yu; Xu, Jian; Liu, Qin (Frontiers in Microbiology, 2022)
The rhizosphere microbe Pseudomonas protegens FD6 possesses beneficial traits such as the production of antibiotics like pyoluteorin (Plt) and 2,4-diacetylphloroglucinol (2,4-DAPG). The alternative RpoS (σ38 factor), as a master regulator, activates or inhibits the transcription of stationary phase genes in many biocontrol organisms. Here, we investigated the complicated function and regulatory mechanism of RpoS in the biosynthesis of 2, 4-DAPG and Plt in strain FD6. Phenotypic assays suggested that ΔrpoS was impaired in biofilm formation, swimming motility, swarming motility, and resistance to stress, such as heat and 12% ethanol. The RpoS mutation significantly increased both 2,4-DAPG and Plt production and altered the transcription and translation of the biosynthetic genes phlA and pltL, indicating that RpoS inhibited antibiotic production by FD6 at both the transcriptional and translational levels. RpoS negatively controlled 2,4-DAPG biosynthesis and transcription of the 2,4-DAPG operon phlACBD by directly interacting with the promoter sequences of phlG and phlA. In addition, RpoS significantly inhibited Plt production and the expression of its operon pltLABCDEFG by directly binding to the promoter regions of pltR, pltL and pltF. Further analyses demonstrated that a putative R147 mutation in the RpoS binding domain abolished its inhibitory activity on the expression of pltL and phlA. Overall, our results reveal the pleiotropic regulatory function of RpoS in P. protegens FD6 and provide the basis for improving antibiotic biosynthesis by genetic engineering in biocontrol organisms.